Método de aprendizagem por projectos no ensino de Física em Moçambique - Victorino, Alfiado (2006)
Several times, in conversation with students, I felt certain disenchantment between them and lhe curricular Physics subject When lhe present essay gol into lhe student's role in lhe teaching and learning process of Physics subject in lhe Mozambican schools taking as reference two public ones of lhe Beira city namely, "Samora Moisés Machel" Secondary School and "Mateus Sansão Mutemba" Secondary School, intends to understand lhe reasons of "disagreement" between students and Physics subject, on lhe one hand, and suggest some actions to be taken in arder to make lhe Phisics teaching become more relevant and more and more interesting and attractive for lhe students, on lhe olhar hand. Starting trom lhe point that students work less in Physics classes, and afiar they've read some authors concerned with lhe students role in lhe teaching and learning process, such as FREIRE (1987), HERNÁNDEZ (1998), ALMEIDA & JÚNIOR (2004), BORDENAVE & PEREIRA (1997), COLL etal (2001) among others, I led a research in arder to observe, record and analyze lhe students activities in lhe Physics lessons in lhe schools above mentioned. Afterwards, I carried out some lessons trough learning method by project in arder to check lhe contribution of this method in lhe performance growth of lhe students in lhe lessons. The conclusions taken trom this research indicate lhe predominance of verb, rhetoric in lhe Physics lessons beside lhe olhar recommended ways for lhe natural sciences teaching. The work projects carried out at school nevertheless its low quantity and quality mirrar a sign of a way to follow in arder to increase lhe performance levei of lhe students in lhe Physics lessons. Therefore, in lhe context of this research, performance of alllevels teachers and education managers is recommended, in lhe research, identification and implementation of all-embracing teaching methodologies which give privilege to lhe activity of lhe learning person in ali processo